Food for thought: Sub-fossil and fossil chelonian remains from Franchthi Cave and Megalopolis confirm a glacial refuge for Emys orbicularis in Peloponnesus (S. Greece) - Vlachos, Evangelos (2016)
Peloponnesus peninsula (S. Greece) shows a remarkable extant chelonian fauna that has received considerable attention from a molecular and morphological point of view. Here we present new evidence from the fossil and sub-fossil record of two important sites in the area, Franchthi Cave and Megalopolis. The archaeological material from Franchthi Cave (Upper Paleolithic – Neolithic/latest Pleistocene – early Holocene) represents food remains from small game prey of the humans that inhabited the cave. The palaeontological material from Megalopolis (Late Pleistocene) comes from old and new excavations. The studied specimens, combined with information from molecular, climatic and zoological works, provide for the first time direct evidence for the presence of the European pond turtle, Emys orbicularis, in the glacial refuge of South Greece that was hypothesized on the basis of the results of molecular investigations. We also describe other chelonian taxa present in the localities, the Hermann's tortoise Testudo hermanni and the Balkan stripe-necked terrapin Mauremys rivulata, and review previously published chelonian material from Peloponnesus.